Hubungan antara Kadar Asam Urat dengan Profil Lipid pada Pasien Sindrom Koroner Akut di RSUD Sanjiwani Gianyar - I Gusti Ngurah Bayu Paramartha; I Gede Bagus Gita Pranata Putra; Sri Ratna Dewi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
AbstractThe Correlation Between Uric Acid and Lipid Profile in Acute Coronary Syndrome Patient of Sanjiwani Hospital GianyarSeveral studies show that high uric acid levels is linking to the incidence of acute coronary syndromes and dyslipidemia that leads to heart disease. The aim of this study is to determine the association between uric acid and lipid profile in acute coronary syndrome patients of Sanjiwani Hospital Gianyar. Cross-sectional analysis is the type of data analysis that is being used in this study and was conducted at the Sanjiwani Hospital, Gianyar, with a total of 45 subjects involved. Spearman correlation test showed that there was a significant positive correlation between uric acid levels and Total Cholesterol (TC) (r = 0.467 and p = 0.001). There was a significant positive correlation between uric acid levels and Low Density Lipoprotein (LDL) (r= 0.348 and p value = 0.019). There was a significant negative correlation between uric acid levels and High Density Lipoprotein (HDL) (r= -0.445 and p = 0.002). There was no significant correlation between uric acid levels and Triglycerides (TG) (r = 0.232 and p = 0.124). It was also found that more than 50% of subjects had uric acid levels in the high category (53.3%), optimal Total Cholesterol (TC) levels (80%), normal High Density Lipoprotein (HDL) levels (57.8%), and optimal Triglycerides (TG) levels (71.1%). Meanwhile, 46.7% of subjects had optimal Low Density Lipoprotein (LDL) levels.